HAK WARGA NEGARA UNTUK MEMPEROLEH JAMINAN KESEHATAN SEBAGAI UPAYA PERLINDUNGAN PENDUDUK DI KOTA SEMARANG - Yuninda Khayyu Ardila, Amiek Soemarmi, Ratna Herawati (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Based on Constitution of 1945 and Act Number 36, 2009 about health suggests that any individuals, families and sociaty have a right to get protection of their healty, and state is responsible to regulate in order to meet healthy live for their society including poor people. Semarang regency administration already tried to give protection to society related to health assurance through policies that already programmed such Jamkesmas and Jampersal for pregnant woman. Research results showed regulations about health assurance for residents in Semarang, including Local Regulation Number 4, 2008 about proverty solution, Mayor Regulation Number 28, 2009 about Health Care Implementation Direction for poor people in Semarang, and Permenkes No. 2562/Menkes/Per/XII/2011 about Delivery Assurance Technical Direction. Method in order to obtained health assurance in Semarang are by take Jamkesmas Card that already have to the local health care location. Then from health care service implementer will processed and submit the claim to appropriate authorities, namely Health Affairs Department of Semarang.